Utilization of Water Chestnut Activated Chacoal as Peat Water Biofilter Using Three Types of Activators - Khamidah, Noor; Suparto, Hairu; Awalia, Mery (Indonesian Journal of Chemical Science, 2021)
Water chestnut (Eleocharis dulcis) is an underutilized plant by the people of South Kalimantan so its existence is abundant. Water chestnut has the potential as the raw material of activated charcoal to improve peat water quality which is still low. Activation is one of the processes of making activated charcoal which aims to enlarge the pores of the charcoal by oxidizing surface molecules or breaking hydrocarbon bonds. This research aims to determine whether water chestnut-activated charcoal can be used as a peat water biofilter, to determine whether H3PO4, ZnCl2, and KOH can be used as activators of water chestnut activated charcoal, and to determine which type of activated charcoal activator is most effective in purifying peat water. The activators used in this study include H3PO4, ZnCl2, and KOH with a 20% concentration. The making of activated charcoal includes reducing the size of the material, drying, carbonization, activation, activated charcoal washing, and drying. Activated charcoal of water chestnut then used in the peat water filtration process. The results showed that activated charcoal of water chestnut can be used as a peat water biofilter. H3PO4, ZnCl2, and KOH can be used as activators of water chestnut activators. The most effective activator in purifying peat water is 20% of H3PO4.